Research on Key Combination Paths of Influence of Health Bloggers: A Qualitative Comparative Analysis Based on the HSM Model - Lai, Huiyu; Cui, Xi; Shi, Jie (The Journal of Medicine, Humanity and Media, 2024)
This article, based on the heuristic-systematic model theory, integrates the characteristics of content production and dissemination logic of opinion leaders to establish an analytical framework and employs fsQCA to conduct configurational analysis on 100 health-related microblog influencers. The study reveals the following findings: (1) Four paths driving high-level dissemination effectiveness are identified, characterized by a predominance of medical content, low media richness, and high update frequency; high public interpretation, low media richness, and high update frequency; a prevalence of medical content, high public interpretation, and high update frequency; and (2) In the systematic cues, elements such as a preponderance of medical content and high public interpretation emerge as core conditions across different combinations, while low public interpretation and high information originality serve as marginal conditions. Within the heuristic cues, situational elements like low media richness and high update frequency emerge as core conditions across different combinations, while low dialogue loops and high dialogue loops serve as marginal conditions.